Characteristics of Dye-doped Silica Nanoparticles- Based Random Lasers in the Air and Water - Ta, Duong Van; Nguyen, Tam Trong; Mai, Hanh Hong; Nguyen, Thau Xuan; Nghiem, Lien Thi Ha (Communications in Physics, 2021)
Random lasers based on dye-doped silica nanoparticles are attracted for biomedical applications due to their biocompatibility and high brightness. Several laser structures including silica powder and film have been reported. However, the dependence of lasing characteristics including lasing threshold and emission wavelength on the laser size and working environment have not been explored. Here, we demonstrate and compare the lasing characteristics of dye-doped silica random lasers in air and water. These lasers present in thin structures, the so-called microslices, with a thickness of 1 µm and various dimensions from 30 to 300 µm. It is found that the lasing threshold (Ith) decreases with increasing laser size such as  for sample in the air and  for sample in water, where A the sample surface area. For a similar size, the lasing threshold of the sample in water is about 3-8 times higher than that of the sample in the air. In addition, the lasing peak wavelength exhibits a red-shift with increasing laser size. In the air, a shift of 8 nm is recorded when the sample surface area increases from 21×103 to 169×103 µm2. Furthermore, for a similar size, the lasing wavelength of the sample in the air is also red-shifted (13 nm in average ) compared with that of the sample in water. Our finding provides useful information for the use of silica-based random lasers in bioimaging and biosensing applications.